Effect of intraoperative intravenous remimazolam on the postoperative quality of recovery after noncardiac surgery: A meta-analysis of randomized controlled trials - Huan Liu; Mingxia Zhou; Xiangdong Chen; Elham Esmaeili; Meng Sun; Zhilin Wu (PLoS ONE, 2025)
Objectives The postoperative quality of recovery holds significant economic and prognostic implications. Numerous studies have investigated the postoperative quality of recovery following surgery. However, the impact of intraoperative intravenous remimazolam on postoperative recovery has yielded conflicting results. Methods In this qualitative review of randomized controlled clinical trials assessing the use of intraoperative remimazolam, we present the effects of intravenous remimazolam on postoperative recovery quality in noncardiac surgery patients. We conducted a comprehensive search of PubMed, MEDLINE, Web of Science and Cochrane Library for randomized controlled trials published up to September 23, 2024, without any language restrictions, to investigate the impact of intraoperative intravenous remimazolam on the quality of postoperative recovery following noncardiac surgery. The primary outcome measure was the quality of postoperative recovery assessed using global QoR-40 scores or QoR-15 scores. Secondary outcomes included five dimensions of quality of postoperative recovery: physical comfort, emotional state, physical independence, psychological support, and pain. As well as time to extubation, VAS score, PACU stay, and days in hospital. We analyzed the pooled data using a random-effects model. Results This meta-analysis included 18 studies published between 2022 and 2024 involving 1720 patients. The quality of postoperative recovery was assessed using the QoR-15 or QoR-40 questionnaires. The pooled results showed no significant difference in QoR scores between the two groups on the first postoperative day (SMD =  0.12; 95% CI -0.13-0.36; I2 = 78%; p =  0.35). Furthermore, differences in QoR dimensions, PACU duration, extubation time, and length of hospital stay were not observed. Conclusion Our analysis showed that the quality of recovery after general anaesthesia in the remimazolam group was similar to that of conventional sedation. Therefore, remimazolam may be used as a potential anaesthetic agent as an alternative to conventional sedation for non-cardiac surgical anaesthesia.